Tool Use Contraception Implants on Knowledge of Couples of Childbearing Age in the Mamuju Community Health Center Work Area - Susiandari, Ariawati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The high rate of female deaths due to complications during or after pregnancy and childbirth indicates global inequalities in quality health services. The contraceptive needs of 214 million women of childbearing age in 2017 in developing countries have not been met due to several reasons, including limited access to services, limited choice of methods, side effects, culture, religion and limited information. This research uses an analytical observational study with a cross-sectional study design, which is research to study the dynamics of the correlation between risk factors and effects, using an approach, observational method, or data collection, where the sample is taken using a multistage sampling technique because it is easier to do. This type of multistage sampling is carried out at the regional level in stages. The results of this study show that there is a relationship between the level of knowledge of reproductive age couples and the use of contraceptive implants. From the results of this research, it can be concluded that the level of knowledge influences the attitudes of couples of childbearing age in choosing and determining which contraceptive implants to use currently.